Transformation of the retaining wall external geometry with rationalizing of system parameters - Kalmykov, Oleg; Khalife, Rabih; Demianenko, Ivan (Academic journal Industrial Machine Building Civil Engineering, 2020)
The article presents the variable task formulation and implementation of finding a rational outline of the waiting wall back face. In the Coulomb theory framework, an analysis is made of a system consisting of a retaining structure and soil pressing on it for the formulating a rational design problem possibility. The possibility of formulating the problem of finding the rational rear face geometry of the retaining wall within a given horizontal projection is shown. The substantiation of the energy rationalization method operation in solving the problem under consideration is given. The proposed approach allows a variable method to determine the surface configuration of the retaining wall, rational from the standpoint of the accepted criterion. The example given in the work clearly proves the correctness of the problem and its solution statement.
Keywords: retaining wall; curved surface; approximation; algorithm construction; variation approach